POTENSI MALTODEKSTRIN BIJI NANGKA SEBAGAI ENKAPSULAN PADA MIKROENKAPSULASI REDESTILAT ASAP CAIR - , INDAH KURNIAWATI, Prof. Dr. Ir. Purnama Darmadji, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Redistillated liquid smoke is highly potential antioxidant and natural preservative due to its bioactive compounds, but prone to deterioration during storage, handling, and distribution, thus need to be protected. Microencapsulation is commonly used method. This study aimed to evaluate redistillated liquid smoke microcapsule characteristic, prepared using total soluble solid from jackfruit seed maltodextrine and various spray drying inlet temperature, based on total phenolic and encapsulation efficiency, as well as to evaluate optimum treatment based on highest efficiency, to attain high quality microcapsule. Microencapsulation was prepared using jackfruit seed maltodextrine as wall material with 20, 25, 30% total soluble solid variation and 120, 130, 140Â°C spray drying inlet temperature variation and feed flow rate of 5 mL/minute. Evaluation parameters were phenolic staining analysis using optilab, moisture content, solubility, total phenolic compound, encapsulation efficiency, shape and morphology using Scanning Electron Microscopy (SEM), particle size distribution and volatile profile identification using GC-MS, data was taken triplicate for all parameters using completely randomized experiment design. The results showed that jackfruit seed maltodextrine can encapsulate phenolic compound of redistillated liquid smoke based on optilab analysis using FeCl3 indicated phenol red in the microcapsule. Higher concentration of total soluble solid and inlet temperature can increase the yield, solubility and encapsulation efficiency. The best results with highest efficiency 47.44 Â± 1.93% and 1 minute solubility obtained using 30% jackfruit seed maltodextrine with 140Â°C inlet temperature. Total phenol increase after drying based on GC-MS analysis with microparticle and microcapsule total phenol of 9.50% and 14.25%, respectively. SEM analysis showed that particleâs shape was spherical with smooth and aglomerated surface area, and microcapsule average size of 3.9 Î¼m.